The Role of Citizenship Education in the Implementation of Pancasila Values for Students in Elementary Schools - Ramadani, Wulan (International Journal of Students Education, 2024)
Education on the role of citizenship education in the implementation of Pancasila values in elementary schools using qualitative methods. The researcher will search for and review literature related to the role of Pancasila Education in shaping the character of students in schools. The sources used include books, articles, research reports, and other related sources. The samples in this study are literature sources related to the research, which include journal articles, books, research reports, and other sources relevant to the research. Sample selection was carried out by searching for literature through electronic databases such as scientific journals. Data analysis used triangulation. from the research it is stated that citizenship education has an important role for elementary school children in instilling the implementation of Pancasila values in elementary school students.